2021
DOI: 10.3389/fnagi.2021.724064
|View full text |Cite
|
Sign up to set email alerts
|

Dance Intervention Impact on Brain Plasticity: A Randomized 6-Month fMRI Study in Non-expert Older Adults

Abstract: Background: Dance is a complex activity combining physical exercise with cognitive, social, and artistic stimulation.Objectives: We aimed to assess the effects of dance intervention (DI) on intra and inter-network resting-state functional connectivity (rs-FC) and its association to cognitive changes in a group of non-demented elderly participants.Methods: Participants were randomly assigned into two groups: DI and life as usual (LAU). Six-month-long DI consisted of supervised 60 min lessons three times per wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Dance affords significant improvements in brain chemistry, architecture, and performance such that physical health, neurocognition, and physical function can be maintained for a better quality of life [54,[56][57][58][59][60][61]72,118,119,126]. "Dance showed a better effect for structural and functional changes in the brain" than music and exercise [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dance affords significant improvements in brain chemistry, architecture, and performance such that physical health, neurocognition, and physical function can be maintained for a better quality of life [54,[56][57][58][59][60][61]72,118,119,126]. "Dance showed a better effect for structural and functional changes in the brain" than music and exercise [58].…”
Section: Discussionmentioning
confidence: 99%
“…A small RCT [119] with healthy people more than 60 years old compared a control group living "life as usual" to a 60 min, 3 times a week, dance intervention group. Irish country, African, Greek, and other types of dances were included with medium physical intensity; enhanced brain activity on resting state fMRI with the dance intervention correlated with improved attention and executive functions.…”
Section: Dancementioning
confidence: 99%
“…According to comprehensive reviews, dance could promote plasticity in functional and structural brain networks (Basso et al, 2021b;Teixeira-Machado et al, 2019). Recent interventional studies in older adults confirmed partially increased functional connectivity in higher-order systems, including the default mode and frontoparietal networks, in response to 3-, 4-and 6-months dance-based programs, respectively (Balazova et al, 2021;Balbim et al, 2021;Chao et al, 2021). Other studies in similar populations have demonstrated improvements after DMI compared to comparators in white matter microstructural integrity of the fornix (Burzynska et al, 2017) and gray matter morphology.…”
Section: Putative Neurophysiological Mechanisms Underlying Psychologi...mentioning
confidence: 99%
“…Aerobic exercise interventions in older adults can increase brain volumes (Erickson et al, 2011), brain-derived neurotrophic factor (BDNF) (Erickson et al, 2011), and organization of functional networks (Burdette et al, 2010;Voss et al, 2010;Baniqued et al, 2017). Emerging evidence suggests that dance may also increase brain volumes (Rehfeld et al, 2018;Rektorova et al, 2020), structural connectivity (Burzynska et al, 2017), BDNF (Rehfeld et al, 2018), and functional connectivity (Zilidou et al, 2018;Balazova et al, 2021) in older adults.…”
Section: Introductionmentioning
confidence: 99%